The Importance of English Language Skills in Mechanical Engineering Education: A Literature Review - Putra, Tri Mandala (English Language Teaching for EFL Learners Journal, 2025)
This literature review explores the significance of English language proficiency in mechanical engineering education. The objective is to analyze how English skills impact academic achievement, access to technical resources, and graduates’ employability in the global workforce. The study uses a qualitative approach, reviewing recent scholarly articles and reports on English for Specific Purposes (ESP) in engineering. Findings indicate that English proficiency is crucial for understanding technical literature, participating in international collaborations, and increasing job opportunities. The review concludes that integrating English into the mechanical engineering curriculum is essential to prepare students for both academic and professional success.